THE IMPORTANCE OF A SENSE OF PURPOSE FOR SALESPERSONS: MORE THAN JUST A FINANCIAL ASPECT - Aripin, Zaenal; Agusiady, Ricky; Ariyanti, Maya (Journal of Economics, Accounting, Business, Management, Engineering and Society, 2024)
In a competitive business environment, the role of a salesperson is not only limited to achieving financial targets, but also involves creating strong relationships with customers and contributing to the company's long-term goals. In this context, it is important to understand the role of a sense of purpose as a powerful motivator for salespeople, which goes far beyond just the financial aspect. This research aims to explore the importance of a sense of purpose for salespeople and its impact on performance, customer relationships and mental well-being. The research method used is qualitative with a descriptive analysis approach. Data was obtained through in-depth interviews with salespeople from various industries and content analysis of relevant literature. The research results show that a sense of purpose plays a key role in increasing sales force motivation, performance, and job satisfaction. Additionally, a sense of purpose also influences customer relationships, with salespeople who have a strong sense of purpose tending to be more caring and empathetic towards customer needs. Additionally, a sense of purpose is also linked to mental wellbeing, with salespeople who have a clear sense of purpose tending to have lower stress levels and better mental wellbeing.